A NOTE ON CAUSALITY RELATIONS AMONG ECONOMIC_x000D_ GROWTH, DEVELOPMENT ASSISTANCE AND TRADE_x000D_ OPENNESS IN LOW INCOME COUNTRIES - TEKİN, RIFAT BARIŞ (My University, 2020)
This article tests for causality relations among economic growth, official development assistanceand openness-to-trade in low income countries. A recently developed Granger causality testingmethodology based on Bayesian estimation of Seemingly Unrelated Regression (SUR) systems isemployed in this study. Findings suggest a direct, unidirectional causality from official developmentassistance to economic growth in Chad, Madagascar, Democratic Republic of the Congo, the Gambiaand Sierra Leone. In Chad and the Gambia, regression coefficients are found to be negative, suggestinga negative impact of foreign aid on economic growth. We therefore fail to provide clear-cut empiricalevidence in support of aid effectiveness. Test results suggest unidirectional causality from opennessto-trade to economic growth in Chad, Democratic Republic of the Congo, the Gambia, Rwanda, Mali,Niger and Togo. In all these countries, except Democratic Republic of the Congo, the mean estimationbeta is positive, providing some support for the trade-led growth hypothesis. For Chad, Rwanda,Malawi and Madagascar we find evidence for positive, unidirectional causality in reverse direction,that is, from economic growth to openness-to-trade. Finally, in Benin, Burkina Faso and Mali we findevidence that foreign aid inflows Granger-cause and enhance openness-to-trade.

Bu makale düşük gelirli ülkelerde resmi kalkınma yardımları, ticari açıklık ve iktisadi büyüme_x000D_ arasındaki muhtemel nedensellik ilişkilerini inceliyor. Makalede, Görünürde İlişkisiz Bağlanımların_x000D_ Bayesçi Tahminine dayalı bir nedensellik testi yaklaşımı kullanılarak 14 düşük gelirli ülkenin yer_x000D_ aldığı bir panelde değişkenler arasındaki tek ve çift yönlü nedensellik ilişkileri test ediliyor. Elde_x000D_ edilen test sonuçları Çad, Madagaskar, Kongo Demokratik Cumhuriyeti, Gambiya ve Sierra Leone’de_x000D_ resmi kalkınma yardımları ile iktisadi büyüme arasında anlamlı bir nedensellik ilişkisi bulunduğunu_x000D_ düşündürüyor. Çad ve Gambiya için regresyon katsayılarının negatif olması bu iki ülke örneğinde_x000D_ kalkınma yardımlarının büyümeyi olumsuz etkilediğine işaret ediyor. Çalışmada elde edilen bulgular_x000D_ Çad, Gambiya, Ruanda, Mali, Nijer ve Togo’da ticari açıklık ile iktisadi büyüme arasında tek yönlü_x000D_ nedensellik ilişkileri bulunduğunu, bu ülkelerde ticari açıklık arttıkça büyümenin olumlu yönde_x000D_ etkilendiğini gösteriyor. Diğer taraftan, çalışmada elde edilen bulgular Çad, Ruanda, Malavi ve_x000D_ Madagaskar’da büyümenin ticari açıklığı tetiklediğine işaret ediyor. Elde edilen test sonuçları kalkınma_x000D_ yardımları ile ticari açıklık arasında anlamlı nedensellik ilişkilerinin bulunduğunu; Benin, Burkina_x000D_ Faso ve Mali’de yardımların ticari açıklığı arttırdığını gösteriyor.
DÜŞÜK GELİRLİ ÜLKELERDE İKTİSADİ BÜYÜME, KALKINMA YARDIMLARI VE TİCARİ AÇIKLIK ARASINDAKİ NEDENSELLİK İLİŞKİLERİ ÜZERİNE BİR DEĞERLENDİRME